Use of indicators of standards of care to improve tuberculosis program management in Ethiopia. (January 2018) - Melese, Muluken; Habte, Dereje; Girma, Belaineh; Kassie, Yewulsew; Negash, Solomon; Melkeneh, Kassahun; Daba, Shallo; Negussie, Gebre; Haile, Yared Kebede; Jerene, Degu; Hiruy, Nebiyu; Gashu, Zewdu; et al.
Abstract: Background: Systematic monitoring of health programs and on-site mentoring of health workers are essential for the success of health care. This operations research was designed to measure the effectiveness of a new mentorship and supervisory tool for supervisors. Methods: In 2011 the Help Ethiopia Address the Low TB Performance (HEAL TB) Project used WHO or national TB indicators as standards of care (SOC) for baseline assessment, progress monitoring, gap identification, assessment of health workers' capacity-building needs, and data quality assurance. Cut-off points were selected for poor, average, and best performers for each indicator. In this analysis we present results from 10 zones (of 28) in which 1, 165 health facilities were supported from 2011 through 2015. Other zones were excluded from the analysis because they entered the project later. The data were collected by trained mentors/supervisors and entered into Microsoft Excel. We used rates and ratios to show the impact of the intervention. Results: The improvement in the median composite score of 13 selected major indicators (out of 22) over four years was significant ( p  = 0.000). The proportion of health facilities with 100% data accuracy for all forms of TB was 55.1% at baseline and reached 96.5%. In terms of program performance, the TB cure rate improved from 71% to 91.1%, while the treatment success rate increased from 88% to 95.3%. In the laboratory area, where there was previously no external quality assurance (EQA) for sputum microscopy, 1, 165 health facilities now have quarterly EQA, and 96.1% of the facilities achieved a ≥ 95% concordance rate in blinded rechecking. Conclusion: The SOC approach for supervision was effective for measuring progress, enhancing quality of services, identifying capacity needs, and serving as a mentorship and an operational research tool.